Can strain gauge replace force plate to measure gymnast relative strength on still rings? - Lecocq, T.; Mochizuki, L.; Tordi, N. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Still rings routine has evolved during the last century toward more and more strength. The gymnast`s relative strength is paramount to overcome the effect of gravity with his own upper limbs` features. Authors measured upper limb relative strength with force plates placed under the gymnast (Bango, 2013, 2017) or under his hands` palm (Dunlavy, 2007) in various positions. Despite being the gold standard, force plates are big, heavy, and expensive pieces of material for a gymnastic association interested in the relative strength measurement. The aim is to quantify how accurately a pair of strain gauges placed in the cables can measure the vertical force produced by gymnasts. METHODS: 14 gymnasts (32 ± 11 years, 74,5 ± 7,1 kg, 172,6 ± 6,4 cm) performed 19 maximal isometric contractions in the iron cross position. After measuring the gymnast`s arm span with shoulder at 90° and hands in the rings, the following instruction were given "Try to lift your body for 5 seconds by pushing your hands down while maintaining straight arm". Gymnasts stood on two force plates (K-Deltas, Kinvent, Montpellier) to measure the vertical ground reaction force (vGRF) at rest and during the maximal contraction task. The cable load (Tension) was measured by a pair of one-dimension strain gauges (K-Pull, Kinvent, Montpellier) attached to the rings cable, rigged on a high bar, 50 cm apart. vGRF and Tension were synchronously recorded on a tablet with the manufacturer software at a frequency of 1 kHz. Signals were smoothed with a 100ms window moving average. The angle between the vertical and the cable was calculated using : Angle=sin-1(((Armspan-50)/2)/(Cable length)) and the vertical component of the cable force was corrected with : vForce = (cos(Angle))×Tension. Right and left vForce were summed (total vForce) and a mean value over 2-seconds in the middle of the contraction was compared with vGRF. The linear correlation between both methods` mean value (total vForce and vGRF) were calculated using Pearson´s r. Bland-Altman plot was utilized to check the agreement and paired-sample Student T-Test to quantify the differences between total vForce and vGRF. RESULTS: Total vForce and vGRF are correlated (R=0.99). The strain gauge method presents a systematic error of -0.42 kg (P < 0.001) and a 95% confidence interval of 1.15 kg compared to the force plate. CONCLUSION: The systematic under-estimation might be explained by the discrepancy between the arm span measurement position and the maximal contraction position. By removing 5 cm to all athletes` arm span, the systematic error decreases to -0.12 kg (P = 0.068), with a 1.02 kg confidence interval. The 2.5 cm reduction on each side could be explained by scapula retraction, slight arms bending and hands position modification. The strain gauges are a valid tool to measure the upper limb relative strength provided that the arm span doesn`t change during the contraction since it affects the angle of the cable and therefore the vertical component of the force.